Global research trends of Mycoplasma pneumoniae pneumonia in children: a bibliometric analysis - Song, Zhe; Jia, Guangyuan; Luo, Guangzhi; Han, Chengen; Zhang, Baoqing; Wang, Xiao (Frontiers in Pediatrics, 2023)
Mycoplasma pneumoniae (MP), represents a predominant form of community-acquired pneumonia in pediatric populations, thereby posing a significant threat to pediatric health. Given the burgeoning volume of research literature associated with pediatric MPP in recent years, it becomes imperative to undertake a bibliometric analysis aimed at delineating the current research landscape and emerging trends, thereby furnishing a framework for subsequent investigations. Methods: A comprehensive literature search targeting pediatric MPP was conducted in the Web of Science Core Collection. After the removal of duplicate entries through Endnote software, the remaining articles were subject to scientometric analysis via Citespace software, VOSviewer software and R language, focusing on variables such as publication volume, contributing nations, institutions and authors, references and keywords. Results: A total of 1,729 articles pertinent to pediatric MPP were included in the analysis. China and the United States emerged as the nations with the highest publication output. Italian scholar Susanna Esposito and Japanese scholar Kazunobu Ouchi were the most influential authors in the domain of pediatric MPP. Highly-cited articles primarily focused on the epidemiological investigation of pediatric MPP, the clinical characteristics and treatment of macrolide-resistant MPP, and biomarkers for refractory Mycoplasma pneumoniae pneumonia (RMPP). From the corpus of 1,729 articles, 636 keywords were extracted and categorized into ten clusters: Cluster #0 centered on molecular-level typing of macrolide-resistant strains; Cluster #1 focused on lower respiratory tract co-infections; Clusters #2 and #6 emphasized other respiratory ailments caused by MP; Cluster #3 involved biomarkers and treatment of RMPP; Clusters #4 and #9 pertained to extrapulmonary complications of MPP, Clusters #5 and #7 addressed etiological diagnosis of MPP, and Cluster #8 explored pathogenic mechanisms. Conclusions: The past few years have witnessed extensive attention directed towards pediatric MPP. Research in pediatric MPP principally revolves around diagnostic techniques for MP, macrolide resistance, complications of MPP, treatment and diagnosis of RMPP, and elucidation of pathogenic mechanisms. The present study provides pediatric clinicians and researchers with the research status and focal points in this field, thereby guiding the orientation of future research endeavors.